EFFECTS OF CURRENCY FLUCTUATION AND HERDING BEHAVIOR ON EMERGENCE OF BULL AND BEAR MARKETS IN TEHRAN STOCK EXCHANVE - Abbasi Shehni, Samira (Gênero & Direito, 2020)
This study analyzed the effects of currency fluctuations and herding behavior of investors on the emergence of bull and bear markets in 36 industries listed in the Tehran Stock Exchange. The Christie-Huang model (1995) and the Kalman filter were employed to evaluate herding behavior and currency shock, respectively, in order to detect the days on which these fluctuations acted as anomalous pulses. In addition, the logistic regression was utilized to analyze and predict bull and bear markets because the dependent variable was dichotomous. According to the results, herding behavior had no effects on the market trend and emergence of bull and bear markets; however, currency fluctuations showed very slight effects.